Formal and informal support for Croatian and Serbian people with disabilities and their families: A scoping review - Čolić, Marija; Buljevac, Marko (Specijalna edukacija i rehabilitacija, 2023)
Introduction. Formal and informal support are important for quality of life of people with disabilities and their families. Objective. The aim of this paper was to (a) identify types of and satisfaction with support for Croatian and Serbian people with disabilities (PWD) and their caregivers and (b) summarise the effects of support reported by PWD and/or their caregivers in Croatia and Serbia. Methods. A systematic search was conducted, followed by eligibility screening of the peer-reviewed articles published from 2000 to June 2020. EBSCOhost, Hrčak, and the Serbian Citation Index [Srpski Citatni Indeks] databases were searched. We also searched the grey literature using Google Scholar and employed backward reference searching. The authors scanned articles and extracted the data related to the country, study’s aim, study’s design, sample, methodology, and findings. Twenty-seven studies were included in this review. Results. Croatian and Serbian PWD and their caregivers received informational, emotional, practical, and financial support at different degrees. They were most satisfied with informal support, while the degree of satisfaction with formal support varied. They highly valued support programs. Conclusion. Croatia and Serbia, in general, lack a formal support system, and informal support is the most prevalent for PWD and their caregivers. There is a need for more support programs for families of PWD.